2008
DOI: 10.2147/copd.s4069
|View full text |Cite
|
Sign up to set email alerts
|

Early discharge care with ongoing follow-up support may reduce hospital readmissions in COPD

Abstract: Background: Early discharge care and self-management education, although effective in the management of chronic obstructive pulmonary disease (COPD), do not typically reduce hospital re-admission rates for exacerbations of the disease. We hypothesized that a respiratory outreach programme that comprises early discharge care followed by continued rapid-access out-patient support would reduce the need for hospital readmission in these patients. Methods: Two hundred and forty-six patients, acutely admitted with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…1 International evidence surrounding chronic disease presentations has revealed that moving from reactive management to proactive management with improved communication demonstrated an increase in complex specialist nursing interventions and led to a decrease in emergency presentations and bed use at local hospitals. 3,7,[15][16][17] A systematic review conducted in 2016 confirmed from several empirical studies that case management roles can be effective in reducing ED usage for adults with chronic illnesses. 18 The WHO has called for planned ongoing assessment, care and support coordinated by a proactive investment in real time solutions that address the increasing burden of this disease on the healthcare sector.…”
Section: What Is Already Known About the Topic?mentioning
confidence: 98%
“…1 International evidence surrounding chronic disease presentations has revealed that moving from reactive management to proactive management with improved communication demonstrated an increase in complex specialist nursing interventions and led to a decrease in emergency presentations and bed use at local hospitals. 3,7,[15][16][17] A systematic review conducted in 2016 confirmed from several empirical studies that case management roles can be effective in reducing ED usage for adults with chronic illnesses. 18 The WHO has called for planned ongoing assessment, care and support coordinated by a proactive investment in real time solutions that address the increasing burden of this disease on the healthcare sector.…”
Section: What Is Already Known About the Topic?mentioning
confidence: 98%
“…COPD PROGRAMS There is growing evidence that outpatient programs that provide education and medical support significantly reduce the rate of hospitalizations for COPD. [16][17][18] Patient education includes symptom monitoring, early recogni-tion of an exacerbation, appropriate use of inhalers and nebulizers, and advice on smoking cessation. 16 On the other hand, a Veterans Administration randomized controlled trial was stopped early because of a higher rate of death in the group that underwent a comprehensive caremanagement program of COPD education, an action plan for identification and treatment of exacerbations, and scheduled proactive telephone calls for case management.…”
Section: ■ Patient Education and Outpatientmentioning
confidence: 99%
“…[16][17][18] Patient education includes symptom monitoring, early recogni-tion of an exacerbation, appropriate use of inhalers and nebulizers, and advice on smoking cessation. 16 On the other hand, a Veterans Administration randomized controlled trial was stopped early because of a higher rate of death in the group that underwent a comprehensive caremanagement program of COPD education, an action plan for identification and treatment of exacerbations, and scheduled proactive telephone calls for case management. 19 Further study is needed to investigate the cost-effectiveness and safety of COPD management programs and whether to adopt such programs on a systematic level.…”
Section: ■ Patient Education and Outpatientmentioning
confidence: 99%
“…Aspects such as providing additional support and testing would not have been possible without a face‐to‐face approach. Furthermore, there is existing evidence are effective at increasing compliance with treatment recommendations, with single home visits by multidisciplinary teams having been effective in increasing asthma patients' adherence to maintaining inhaler use and reduced healthcare utilization a year after the intervention, and other studies showing multiple home visits by nurse practitioners or other trained health practitioners resulting in improved health outcomes (Ghimire et al., 2021; Lawlor et al., 2009; Shelledy et al., 2009; Trilla et al., 2018).…”
Section: Introductionmentioning
confidence: 99%